ANALISIS EFISIENSI TEKNIS USAHA TANI KELAPA SAWIT PENDEKATAN FUNGSI PRODUKSI STOCHASTIC PRONTIER - Marjoni, Stepanus Joni; Suyatno, Adi; Maswadi, Maswadi (Universitas Tribhuwana Tunggadewi, 2025)
Independent oil palm farmers in Landak Regency face challenges in managing production inputs, such as suboptimal fertilization schedules, types, and dosages, which may affect productivity and technical efficiency. This study aims to analyze the technical efficiency of independent oil palm farming in Landak Regency using a stochastic frontier production function approach. The study employed a quantitative approach with a purposive sampling technique, involving 50 independent oil palm farmers. Data were analyzed using the stochastic frontier production function with Maximum Likelihood Estimation (MLE). The average technical efficiency of independent oil palm farming in Landak Regency was 0.921 (92.1%). Input variables such as land area, dolomite fertilizer, and labor had a significant positive effect on production, while NPK fertilizer and herbicide did not show significant effects. Inefficiency factors such as farmer age, education, and experience were not statistically significant. Independent oil palm farming in Landak Regency is technically efficient. To enhance productivity, farmers are encouraged to optimize the use of land, dolomite fertilizer, and labor, while improving NPK fertilizer dosage and pesticide application practices.